Development of Ground Freezing System for Undisturbed Sampling of Granular Soils - Youngseok Kim; Bumsik Hwang; Wanjei Cho (Advances in Civil Engineering)
The ground freezing technique was first invented for the undisturbed sampling of the granular soils. With increasing necessity of liquefaction evaluation under earthquake loading, there has been more research with high-quality granular samples, with ground freezing techniques in the world. However, there has been little research on the ground freezing techniques since Korea had no records of liquefactions until the Pohang earthquake in 2017. Since more than 10 places were reported with liquefaction phenomena, it is required to assess the liquefaction potential with high-quality samples of granular soils. Therefore, in order to obtain undisturbed samples of granular soils, a new local ground freezing equipment and an operating system were developed in this study. The applied coolant was liquid nitrogen and circulated through a double tube inserted in the ground. To evaluate the performance of the system, laboratory scale tests were performed with water only and saturated fine sands. In the laboratory evaluation, a frozen soil column of 60 cm diameter was made after 20 hours and the average freezing rate was approximately 12 mm/hr in radial direction. After laboratory evaluation, the freezing system was applied in the field and the performance was evaluated with the 2D electrical resistivity tomography. In the field evaluation, the frozen region was 4 m diameter with 6.5 m depth in a cylindrical shape.